Formal radical cyclization onto benzene rings--a general method proceeding via cross-conjugated dienones. - Clive, D; Fletcher, S; Zhu, M (2003)
Cross-conjugated dienones of type 5 (X = I), which are readily available from phenols, undergo radical cyclization (5 --> 6 --> 7), and the products are easily aromatized (7 --> 8), giving substances that are formally derived by radical cyclization onto a benzene ring (cf. eqn. (1)).